The Concept of Geometry in Penataran Temple - Elly Susanti; Arum Permata Rahmadhani (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
This study aims to describe the results of exploring the shapes in Penataran Temple, cultural relics accompanied by geometric concepts. This research uses explorative-descriptive research because it is suitable for uncovering mathematical cases related to Ethnomathematics. The data analysis technique used in this research is qualitative. In this study, an ethnographic approach was used, accompanied by interviews, collecting documentation, or analyzing literature about Penataran Temple as data collection techniques. This study concludes that the relationship between culture and building structure in Penataran Temple has always been attached to the concept of geometry in the material. Wake up flat and build space. In these buildings, the forms are applied in mathematical objects such as in flat plane geometry and space shapes. As in this study results, there are several structures, namely cuboid and right triangular prism and plane shape, in an isosceles triangle.